-3x-y+2z=-6
2x+y-z=3
x-2y+z=1
Soluções para a tarefa
Respondido por
1
Ola Faby
-3x - y + 2z = -6
2x + y - z = 3
x - 2y + z = 1
z = 2x + y - 3
2z = 4x + 2y - 6
-3x - y + 4x + 2y - 6 = -6
x + y = 0
x - 2y + 2x + y - 3 = 1
3x - y = 4
x + y = 0
3x - y = 4
4x = 4
x = 1
y = -1
z = 2x + y - 3
z = 2 - 1 - 3 = -2
S = {(x, y, z), (1, -1, -2)}
-3x - y + 2z = -6
2x + y - z = 3
x - 2y + z = 1
z = 2x + y - 3
2z = 4x + 2y - 6
-3x - y + 4x + 2y - 6 = -6
x + y = 0
x - 2y + 2x + y - 3 = 1
3x - y = 4
x + y = 0
3x - y = 4
4x = 4
x = 1
y = -1
z = 2x + y - 3
z = 2 - 1 - 3 = -2
S = {(x, y, z), (1, -1, -2)}
faby162:
oobgd
Perguntas interessantes